Analysis of Word Order in Chairil Anwar’s Poetry and Its English Translation: - Zulprianto; en_US, Novalinda (Jurnal Penerjemahan, 2015)
This article seeks to analyze the word order of selected lyrics of four poems by Chairil Anwar, and their two English translations by Liaw Yock Fang and Burton Raffel. Word orders are important in any acts of translation, let alone in translating poetry, as they contribute to the thematic systems and especially in the case of poetry, the poetic quality of the lines. Fifteen lyrics are selected to be analyzed using the Skeleton Analysis proposed by Leech et al, which is a simplified notation that can help indicate the layers of structure and, hence, word order of the lyrics in terms of syntactic functions. The results of the analysis show that Fang translates most of the lyrics more faithfully in terms of word orders than Raffel does. Therefore, it follows from this that Fang seems to be able to preserve the thematic system, the poetic effect, or the style of the original in his translation. Key words: poetic quality, thematic system, translation, word order